Employment in Europe 2000. (Employment and social affairs, 2000)
Abstract: The Employment in Europe 2000 Report examines in detail basic elements of the employment challenge in a knowledge based economy renewed in Lisbon summit (March 2000). Beyond recent employment trends in 1999, the Report sets out how each Member State is expected to contribute to achieving the Union's employment objectives. It analyses both the nature and quality of jobs being created, with special focus on its gender dimension and the evolution of social and regional imbalances in the EU. In view of the forthcoming enlargement of the Union, the Report also reviews progress in transforming the labour markets in the Central European candidate countries. Finally, the Report assesses the impact of tax and benefit systems on employment, gauging the tax burden on labour and the tax wedge as well as coverage and replacement rates of unemployment benefits and early retirement systems.